Law enforcement employment discrimination based on sexual orientation: A selective review of case law - Thompson, R. Alan (American journal of criminal justice, 2002)
Homosexuality has been the subject of discrimination from Biblical times through the present. Homosexuals continue to experience pervasive forms of discrimination, including denial of employment which they may be otherwise qualified to obtain. One profession that is particularly open in its discrimination against homosexual employees is law enforcement. This article traces the development of homosexuals’ rights as they specifically relate to employment in law enforcement. Examples of common arguments raised by police administrators to justify such actions are examined with each illustrated by an example from relevant case law. Finally, areas in which the law has begun to provide greater protection for the employment rights of homosexuals are identified.